Enhancing Athlete Profiling Through Technology-Integrated Multiple Hop Testing: Implications for Physiotherapy and Strength and Conditioning - Sharp, Anthony (Auckland University of Technology, 2025)
Multiple hop tests, such as the triple hop (TH) and quintuple hop (QH), are commonly used in strength training, conditioning, and physiotherapy to evaluate lower-limb function, monitor return-to-sport (RTS) progress, and measure athletic performance. Traditionally, these tests quantify total distance jumped, which offers limited insight into movement strategies. Advances in affordable technology, including smartphone videography to computer vision tracking, present opportunities to improve the diagnostic value of these assessments, but their validity, reliability, and practical usefulness are still under-investigated. Given this information, this thesis addressed the overarching question: can technology integration into multiple hop testing provide greater diagnostic insight to better inform physiotherapeutic and strength and conditioning practices? To answer this, the work was structured across four sections, each targeting a specific set of research questions. The current literature on TH and QH tests was reviewed in Section 1, evaluating their reliability, utility, and relationship to performance. Findings highlighted that while the TH is reliable and commonly used, the QH remains under-researched, with limited evidence on its validity and sensitivity. Furthermore, reliance on distance as the sole outcome measure limited diagnostic value, underscoring the need for alternative metrics and accessible technologies to capture movement strategies. The feasibility of smartphone videography for assessing multiple hop performance was investigated in Section 2. Using free software (Kinovea) with tablets and smartphones, strong between-rater (ICC = 0.85-1.00), within-rater (ICC = 0.98-1.00), and test–retest (ICC = 0.47-0.93) reliability for spatiotemporal variables such as flight time, ground contact time, and total time were found. High levels of agreement were found when these variables were compared to gold standard force plates, although small systematic biases were observed. It was established that smartphone-based approaches provided valid, reliable, and cost-effective alternatives for hop diagnostics in field and clinical environments. In Section 3, the physical and biomechanical demands of TH and QH tests, inter-limb asymmetries, and their relationship to sprint performance were explored. Successive hops imposed progressively greater eccentric braking demands, with vertical braking impulses increasing by ~32% and horizontal braking impulses by ~56%, highlighting the importance of graded progression in rehabilitation contexts. Kinetic analyses showed average asymmetries of up to 40% in braking impulses, with some reaching 96%. These asymmetries are often hidden when only using distance outcomes, which averaged 4.7% and peaked at 12.7%. Hop distances correlated strongly with 10-40 m sprint times (r = 0.70-0.80), with reactive strength index horizontal (RSIhor) identified as the strongest predictor of sprint ability (r = 0.49-0.71). Finally, given the high shared variance between TH and QH variables, it is recommended that practitioners use only one of the tests in their assessment battery, the choice of which depends on the injury and athletic status of those being tested. The focus of Section 4 was to translate the research findings of the thesis into applied resources for practitioners, using a “Masterclass” framework to bridge theory and practice. This synthesis provided physiotherapists and strength and conditioning coaches with practical guidance on implementing multiple hop assessments, monitoring asymmetries, and applying hop diagnostics to rehabilitation and performance enhancement. This thesis presents original research that expands the understanding of how multiple hop testing can enhance diagnostic insights in athletic profiling. The findings demonstrate that simple, cost-effective technologies can be effectively integrated into assessments, providing valid and reliable measures of both athlete movement and outcome strategies. Although limitations included cross-sectional designs, male dominated samples, and a focus on TH and QH tasks over other hop-based assessments, the research establishes a framework for incorporating hop assessments into applied practice. Future research should validate emerging technologies like AI-driven video analysis and inertial measurement units, broaden normative data across sexes and performance levels, and explore longitudinal and applied outcomes in clinical and elite sport environments.